Professor-tutor-regente: base de conhecimento e aprendizagens - Borges, Fabiana Vigo Azevedo (2016)
This research investigated the learning faculty of experienced teachers who act as "guardians-rulers" in a "supervised" program developed by the Faculty of Education in UFSCar, in the distance, considering the perspectives of these professionals. Specifically, we would like to to understand the changes in the knowledge base for teaching teachers of educational supervisors to act as placement of student teachers, tutors-regents from their participation program. The literature that supports the study is based on studies of Mizukami (2002, 2004, 2006) and Shulman (1986, 1987, 2005) (knowledge base), Garcia (1999, 2002), Vaillant (2003, 2004), Reali (1995, 2009) (teacher trainer), Pepper and Lima (2002, 2006, 2008) (supervised) and the Distance education as a tool for training of trainers based on Rinaldi (2009), Reali (2009) among others who understand the teacher education as a field to be explored and improved constantly. Through a qualitative study a descriptive-analytical revealed the importance of specific training of teachers to act as supervisors stages of future teachers, or "teacher trainers", and the urgency to score elements that make up the base knowledge for teaching trainer.